Active Control of Aerial Refueling Hose-Drogue Dynamics with the Improved Reel Take-Up System. (19th July 2022) - Cheng, Jiangfeng; Deng, Feng; Liu, Xueqiang; Ji, Kang
Abstract : An improved reel take-up system for suppressing the aerial refueling hose whipping phenomenon (HWP) is proposed and analyzed. The conventional spring-loaded take-up system is improved by adding a rewinding acceleration changing rate limiter (RACRL), relying on a permanent magnet synchronous motor (PMSM). The effectiveness of this new reel take-up system is confirmed by the numerical simulation at various closure speeds. The results show that the new PMSM-RACRL reel take-up system successfully accomplishes the active control of tension oscillation and the suppressing of HWP with a straightforward strategy. The amplitude of tension oscillation is reduced to one-tenth of that without active control. It is also discovered that the reel take-up speed lagging behind the drogue closure speed is mainly caused by the oscillation of hose tension, and a maximum acceleration of the reel take-up system lower than the maximum closure acceleration of the drogue will inevitably cause the slack and whipping of the hose.